Implementation of HACCP system in production of UHT milk - Irena Jeličić (Mljekarstvo)
Regulation of the Croatian Food Law (NN 46/07) which demands implementation of food safety management system based on HACCP principles became mandatory at the January 01st 2009. According to that regulation all subjects in food production and retail sector including the dairy industry too are obligant to implement HACCP system in their production processes. In the process of HACCP implementation many problems occur which result in delaying the implementation, scarce performance of assigned monitoring actions and inadequate maintenance and improvement of the system. All of the latter mentioned problems disable proactive functioning and may lead to disturbance of food safety of the end product. The aim of this paper is to demonstrate the interpretation of each steps that have to be taken in the process of implementation of HACCP system in the production of UHT milk. Thereby many practical informations and examples have been gathered while reviewing the HACCP system in KIM d.d. Dairy industry, Karlovac, Croatia. This paper contains the examples of all indentified hazards, all assigned control actions, hazard analysis and critical control point determination for the process of UHT milk production in KIM d.d. Dairy industry, Karlovac. Furthermore, also examples and ideas for the traceability, verification and validation, product recall and withdrawal procedures are given.